PEMBELAJARAN BERBASIS PROYEK RUMAH ADAT BADUY UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Ramdani, Muhammad; Khaerunnisa, Etika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine whether the improvement in students' mathematical problem-solving ability through Baduy traditional house project-based learning is better than that of students receiving expository learning. This research employed a quasi-experimental method with a pre-test post-test non-equivalent control group design. The population in this study was eighth-grade students of SMPN 3 Kragilan in the 2025/2026 academic year. The sample was selected using a purposive sampling technique, consisting of class VIII D as the experimental group with 33 students and class VIII B as the control group with 32 students. The experimental group implemented Baduy traditional house project-based learning on the topic of flat-sided 3D shapes, whereas the control group utilized expository learning. The research instrument used was a written test consisting of 5 items (pre-test and post-test). Descriptive statistical analysis results showed that the average N-gain score of the experimental group was higher than that of the control group. Furthermore, inferential statistical analysis using the Mann-Whitney U Test was conducted because the N-gain data did not meet the assumptions of normality and homogeneity. Based on the results of the hypothesis testing, it can be concluded that the improvement in mathematical problem-solving ability among students who received Baduy traditional house project-based learning was significantly better than that of students who received expository learning.